Higher Expression of Myosin Heavy Chain IIx in Wrist Flexors in Cerebral Palsy - Gantelius, Stefan (Springer-Verlag, 2011)
BACKGROUND: Children with cerebral palsy (CP) use their paretic arm less than normal but have a relative overactivity of wrist flexors, causing an impairing flexed position of the wrist. Voluntary use of a muscle downregulates myosin heavy chain (MyHC) IIx, but it is unclear whether the relative overactivity of wrist flexors and extensors in children with CP affects MyHC expression compared to normal subjects. QUESTIONS/PURPOSES: We therefore asked whether MyHC expression composition differs in wrist flexors compared to extensors in children with CP and in controls and whether it is related to clinical findings. METHODS: We took muscle biopsies from wrist flexors and extensors during hand surgery in children with CP (n = 9) and during open reduction of forearm fractures in control children (n = 5). The expression of the MyHC I, IIa, and IIx isoforms were determined on silver-stained 6% SDS-PAGE. RESULTS: CP flexors showed a higher proportion of MyHC IIx (40%) than control flexors (16%) and CP extensors (20%). MyHC IIa isoform proportion was lower in CP flexors (27%) than in control flexors (46%) and in CP extensors (45%). MyHC I expression was lower in CP (36%) than in controls (46%) for wrist extensors only. CONCLUSIONS: Both the brain injury in CP and the different demands on flexors and extensors affect the expression of MyHCs. The higher amount of MyHC IIx in CP could be caused by a decreased voluntary use of the hemiplegic arm. CLINICAL RELEVANCE: More information on the structural difference between flexors and extensors in normal and spastic muscle could improve the understanding of strain of wrist extensors and possibly the development of flexion contractures in CP.